2017
DOI: 10.3390/su9081476
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Effects on Soil Quality after Three Years of Irrigation in Northern Spain

Abstract: Abstract:Irrigation is being initiated on large areas of traditionally rainfed land to meet increasing global demand for food, feed, fiber and fuel. However, the consequences of this transition on soil quality (SQ) have scarcely been studied. Therefore, after previously identifying the most tillage-sensitive SQ indicators under long-term rainfed conditions, conversion of a research site on a Haplic Calcisol in Navarre, in northeast Spain provided an ideal location to reevaluate those SQ indicators after three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…In our study, the lack of significant relationships between SQI and crop yields is likely a result of the overall reduced variation in SQI values across rotations and bio‐covers, suggesting that the differences in SQ between treatments were not enough to explain the variation in crop productivity. Moreover, poultry litter increased crop yields across locations (Ashworth et al., 2016a, 2016b; 2017a), but affected negatively SQ in the 0‐ to 15‐cm soil depth (Table 6), particularly under continuous cotton, cotton–corn, and continuous corn rotations (Figure 1). As previously discussed, poultry litter is known as a valuable source of nutrients, but its continuous application may impair water quality due to potential nutrient runoff.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the lack of significant relationships between SQI and crop yields is likely a result of the overall reduced variation in SQI values across rotations and bio‐covers, suggesting that the differences in SQ between treatments were not enough to explain the variation in crop productivity. Moreover, poultry litter increased crop yields across locations (Ashworth et al., 2016a, 2016b; 2017a), but affected negatively SQ in the 0‐ to 15‐cm soil depth (Table 6), particularly under continuous cotton, cotton–corn, and continuous corn rotations (Figure 1). As previously discussed, poultry litter is known as a valuable source of nutrients, but its continuous application may impair water quality due to potential nutrient runoff.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that significant differences were dependent on the model applied for SQ analysis (across depths or per depth). Usually, SQ assessments using SMAF are performed separately per depth (Jokela, Posner, Hedtcke, Balser, & Read, 2011; Karlen, Cambardella, Kovar, & Colvin, 2013; Apesteguia et al., 2017; Cherubin et al., 2016; Veum et al., 2015), due to organic matter and fertility gradients that occur within the soil profile. The absence of significant interactions when analyzing SQ across depths was unexpected, as an increased number of observations ( n = 270) would be more prone to show statistical differences compared with the analysis per depth ( n = 135).…”
Section: Resultsmentioning
confidence: 99%
“…Under field conditions, the chemical and physical effects of irrigation water can vary with several factors [e.g. 2,56,57,58,59] such as drainage provisions, leaching fractions of soil layers, soil tillage conditions (cultivated vs notillage), and also methods of irrigation (flood irrigation, sprinkler or drip irrigation). Combining all these factors in the models, used for predicting the sustainability of irrigation, will be necessary to arrive at a practical approach to mitigate irrigation water effects on soil structure.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
“…In any case, the selection of soil quality indicators needs to be made by simultaneously considering the soil functions and/or the services associated with them that are to be evaluated, and the local conditions imposed by the soil-climatic characteristics at the site under consideration. Some examples of the use of this approach in Navarre, Spain [25,26] for the evaluation of soil quality in agrosystems managed according to conservation agriculture criteria showed that the most appropriate indicators can vary in a relatively short lapse of time with a change of context, such as the transformation from rainfed to irrigated. The identification of these indicators, therefore, must also consider the management context.…”
Section: Introductionmentioning
confidence: 99%